Flavonoids and fibrate modulate apoE4-induced processing of amyloid precursor protein in neuroblastoma cells - Davra, Viralkumar; Benzeroual, Kenza E. (Frontiers in Neuroscience, 2023)
Apolipoprotein (apo) E4, being a major genetic risk factor for Alzheimer's disease (AD), is actively involved in the proteolytic processing of amyloid precursor protein (APP) to amyloid β (Aβ) peptide, the principle constituent of amyloid plaques in Alzheimer Disease (AD) patients. ApoE4 is believed to affect APP processing through intracellular cholesterol homeostasis, whereas lowering the cholesterol level by pharmacological agents have been suggested to reduce Aβ production. This study have investigated the effects of hypolipidemic agents fenofibrate, and the flavonoids -naringenin and diosmetin-on apoE4-induced APP processing in rat neuroblastoma cells stably transfected with human wild-type APP 695 (B103-hAPP695wt). B103-hAPP695wt cells were pretreated with different doses of flavonoids and fenofibrate for 1 hour, prior to apoE4 exposure for 24 h. ApoE4-induced production of intra-and extracellular Aβ peptides has been reduced with all, fenofibrate, naringenin and diosmetin treatments. Pretreatment with diosmetin has significantly reduced, whereas naringenin and fenofibrate had no effect on apoE4-induced full length APP (fl-APP) expression. In addition, the increased in the apoE4-induced secretion of sAPPtotal and sAPPα has been dosedependently reduced with drug pretreatment. On the other hand, the decreased in the expression of both APPcarboxy terminal fragments (CTF)-α and -β (generated by the α-or β-secretase cleavage of APP) by apoE4 was dose-dependently increased in cells pretreated with fenofibrate and naringenin but not diosmetin. Thus, we suggest that fenofibrate, naringenin and diosmetin can reduce apoE4-induced Aβ production by distinct mechanisms that my prove useful to develop drug for AD patients.